A sequence assembly and editing program for efficient management of large projects. - Dear, S (1991)
We describe a sequence assembly and editing program for managing large and small projects. It is being used to sequence complete cosmids and has substantially reduced the time taken to process the data. In addition to handling conventionally derived sequences it can use data obtained from Applied Biosystems,Inc. 373A and Pharmacia A.L.F. fluorescent sequencing machines. Readings are assembled automatically. All editing is performed using a mouse operated contig editor that displays aligned sequences and their traces together on the screen. The editor, which can be used on single contigs or for joining contigs, permits rapid movement along the aligned sequences. Insertions, deletions and replacements can be made in individual aligned readings and global changes can be made by editing the consensus. All changes are recorded. A click on a mouse button will display the traces covering the current cursor position, hence allowing quick resolution of problems. Another function automatically moves the cursor to the next unresolved character. The editor also provides facilities for annotating the sequences. Typical annotations include flagging the positions of primers used for walking, or for marking sites, such as compressions, that have caused problems during sequencing. Graphical displays aid the assessment of progress.